INSECTICIDAL, ANTIMICROBIAL, PHYTO- AND CYTOTOXICITY OF CHASSALIA KOLLY WHOLE PLANT EXTRACT - Onocha, P. A.; Ali, S. M. (African Journal of Traditional, Complementary and Alternative Medicines, 2009)
Chassalia kolly (Schumach.) Hepper (Rubiaceae) is used in ethno-medical practices, particularly in Nigeria and the West African sub-region, for the treatment of typhoid and fevers that are endemic in Nigeria as well as in the tropics. The methanol extract of the dried whole plant Chassalia kolly was investigated for insecticidal, antimicrobial, phyto- and cytotoxicity activities. The extract inhibited the growth of all the bacteria tested in the agar cup plate diffusion technique, exhibiting a concentration dependent activity. Cytotoxicity was evaluated using the brine shrimp lethality assay. The extract was found to be relatively non-toxic as it had an LD50 value greater than 1000 µg/ml. Phytotoxicity tests using the Lemna bioassay revealed a moderate growth inhibitory effect against Lemna minor. The insecticidal assay by contact toxicity method also revealed a moderate insecticidal rate of 40% against Rhizopertha dominica at the concentration of 1572.7 µg/cm2. The extract contained glycosides, alkaloids and flavonoids. Acknowledgement: Senate Research Grant (SRG/FSC/2000/22A), H.E.J. Research Institute of Chemistry, University of Karachi, Karachi, Pakistan.